The new media and its role in disseminating information about the Covid-19 - Alajel, Ahmad mohamad (Journal of Humanities & Social Sciences, 2022)
The aim of the research is to know the role of the new media in disseminating information about the Covid-19 pandemic from the viewpoint of a number of students of the Faculty of Media at the University of Damascus, and to reveal the differences in their perception of its role in disseminating information according to the variables of gender and the academic year. Students of the Faculty of Mass Communication at the University of Damascus from the first and fourth years, and a questionnaire was designed to measure their view of the role of the media in disseminating information about the Covid-19 pandemic, and the research reached the following results:The new media played an important and prominent role in spreading information about the Covid-19 pandemic.- Some of the new media outlets played negatively in disseminating information according to the opinions of the sample members.- There are no statistically significant differences in the perception of the individuals of the research sample of the role of the new media in disseminating information about the Covid-19 pandemic according to the gender variable.- There are no statistically significant differences in the individuals' perception of the research sample of the role of the new media in disseminating information about the Covid-19 pandemic, according to the academic year variable.
Keywords: new media; COVID-19 pandemic